Emerging role of C-peptide as an early biomarker of metabolic syndrome - Usmani, Rana; Masood, Tariq; Kakkar, Kanika; Mishra, Gunjan; Uniyal, Adarsh; Nasa, Udit; Kushwaha, Rajeev Singh (International Journal of Research in Medical Sciences, 2021)
Background: Metabolic syndrome is a health issue of rising concern as it has a correlation with the occurrence of cardiovascular events. Early identification of this syndrome by evaluating levels of biomarkers such as C peptide can help medical professionals prevent the occurrence of life-threatening cardiovascular diseases. Methods: This cross-sectional study was carried out in 89 subjects who were diagnosed to have metabolic syndrome. General Physical examination was done and fasting C peptide and insulin levels were quantified, followed by statistical analysis and their correlation. The prevalence of defining parameters of Metabolic Syndrome as per IDF 2005 was studied. Results: Out of 89 (100%) subjects, 80 (89.8%) subjects (Mean±SD=6.14±3.47) had C- peptide level >1.89 ng/ml which was statistically highly significant (p<0.001). Also, out of 89 (100%) subjects, 67 (24.71%) subjects had insulin level <25 mIU/L which was statistically significant (p<0.001). Conclusions: It was thereby concluded that serum C peptide levels were raised in patients of Metabolic syndrome and it is superior to serum Insulin levels as an early biomarker of the same.